Carbonation of CEM III mortar – Influence of impure CO2 (with SO2 and NO2) and chloride rich brine. (10th November 2020) - Svensson, K.; Neumann, A.; Feitosa Menezes, F.; Lempp, C.; Pöllmann, H.
Highlights: Interaction of mortar specimen with CO2 and chloride rich brine was investigated. Hydration of the CEM III cement (pure water; chloride rich brine) was investigated. Chloride rich brine had no negative impact on the overall reactivity of the cement. Development of compressive strength under varied test conditions was investigated. No measureable negative impact on the compressive strength was observed. Abstract: With regard to CCS (carbon capture and storage) technology, the interaction was investigated of mortar specimen (produced with CEM III) with CO2, featuring small amounts of SO2 and NO2 (each about 70 ppm) in the presence of chloride-rich brine at 333 K and 16 MPa. Chemical and mineralogical properties of the cement were characterized. The mineralogy of hardened cement pastes was evaluated by PXRD (powder X-ray diffraction). DSC-TG (differential scanning calorimetry with thermogravimetry) measurements were carried out and coupled with mass spectrometry (MS). For the evaluation of the mechanical properties mortar prisms (160 mm × 40 mm × 40 mm) were produced according to the German standard DIN EN 196–1:2005. After a hydration time of 29 days, the samples were treated with CO2 in chloride-rich brine at 333 K and 16 MPa for 35 days. The compressive strength of the samples were investigated before and after treatment with impure CO2 and chloride-richbrine. The mortar specimens were treated with CO2 (accompanied with SO2 and NO2 ) in chloride-rich brine (230 g/L NaCl, 15 g/L CaCl2, 5 g/L MgCl2 ) at 333 K and 16 MPa for 35 days. After 35 days in an autoclave the samples seemed to be undamaged by visual inspection. Loss of compression strength was not observed. Due to these promising results further investigation should be considered of the chosen cement system.